Differential Effects of Alzheimer's Disease Aβ40 and 42 on Endocytosis and Intraneuronal Trafficking. (1st March 2018) - Omtri, Rajesh S.; Thompson, Kevin J.; Tang, Xiaojia; Gali, Chaitanya C.; Panzenboeck, Ute; Davidson, Michael W.; Kalari, Krishna R.; Kandimalla, Karunya K.
Graphical abstract: Highlights: Endocytosis genes are downregulated in Alzheimer's brain compared to normal brain. Aβ40 and Aβ42 inhibit the endocytosis of transferrin and LDL by neuronal cells. Aβ40 inhibits the uptake and subsequent accumulation of Aβ42 in lysosomes. Aβ40, more than that of Aβ42, perturbs neuronal trafficking and vesicular dynamics. Abstract: Anomalous neuronal accumulation of Aβ peptides was shown to affect synaptic transmission and contribute to neurodegeneration in Alzheimer's disease (AD) brain. Neuronal cells internalize amyloid beta (Aβ) peptides from the brain extracellular space even under normal physiological conditions, and these endocytotic pathways go awry during AD progression. We hypothesized that exposure to toxic Aβ species accumulating in AD brain contributes to perturbations in neuronal endocytosis. We have shown substantial down-regulation of KEGG endocytotic pathway genes in AD patient brain regions that accumulate Aβ compared to those in non-demented individuals. While both Aβ40 and Aβ42 perturbed endocytosis and intracellular trafficking in neuronal cells, Aβ40 had a greater effect than Aβ42. Moreover, Aβ40 decreased the neuronal uptake and lysosomal accumulation of Aβ42, which tends to oligomerize at low lysosomal pH. Hence, Aβ40 may reduce the prevalence of stable Aβ42 oligomers that are closely associated with neurodegeneration and are intercellularly propagated across the vulnerable brain regions to eventually nucleate as amyloid plaques. In conclusion, elevated brain Aβ levels and Aβ42:40 ratio apparent in the early stages of AD could perturb intraneuronal trafficking, augment the anomalous accumulation of amyloid peptides in AD brain, and drive AD pathogenesis.